2018
DOI: 10.1016/j.freeradbiomed.2018.04.563
|View full text |Cite
|
Sign up to set email alerts
|

A Photo-triggered and photo-calibrated nitric oxide donor: Rational design, spectral characterizations, and biological applications

Abstract: Nitric oxide (NO) donors are valuable tools to probe the profound implications of NO in health and disease. The elusive nature of NO bio-relevance has largely limited the use of spontaneous NO donors and promoted the development of next generation NO donors, whose NO release is not only stimulated by a trigger, but also readily monitored via a judiciously built-in self-calibration mechanism. Light is without a doubt the most sensitive, versatile and biocompatible method of choice for both triggering and monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 48 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…However, there are no reports on 4-nitro-3-(trifluoromethyl)aniline-based NO photoreleaser for antibiofilm application. N -nitrosoamine-based NO donors are also photo-triggered NO donors and several small molecular N -nitrosoamine-based NO donors have been explored [141,142,143,144,145]. More recently, Hu et al reported a NO releasing micelle bearing visible light responsive NO donors [146].…”
Section: No Releasing Polymeric Materials For Antibacterial Applicmentioning
confidence: 99%
“…However, there are no reports on 4-nitro-3-(trifluoromethyl)aniline-based NO photoreleaser for antibiofilm application. N -nitrosoamine-based NO donors are also photo-triggered NO donors and several small molecular N -nitrosoamine-based NO donors have been explored [141,142,143,144,145]. More recently, Hu et al reported a NO releasing micelle bearing visible light responsive NO donors [146].…”
Section: No Releasing Polymeric Materials For Antibacterial Applicmentioning
confidence: 99%
“…[44] With the goal to shift the one-photon absorption towards more biocompatible wavelength, the same group designed compounds 17 and 18 bearing a rhodamine chromogenic core. [45,46] Both non-fluorescent compounds worked very well upon SPE with the biocompatible green light and the NO release can be followed in HeLa cancer cells exploiting the intense red fluorescence of the non-nitrosated by-products. Ultrafast absorption spectroscopy studies carried out on compound 17 confirmed the fast rate of the NO photorelease process, with the homolysis of the NÀ NO bond occurring in less than 7 ps.…”
Section: Latent Fluorescent Photocagesmentioning
confidence: 99%
“…Ultrafast absorption spectroscopy studies carried out on compound 17 confirmed the fast rate of the NO photorelease process, with the homolysis of the NÀ NO bond occurring in less than 7 ps. [45] The feasibility of compound 17 was also studied in mouse mesenchymal stem cells (MSCs), which have attracted great interest due to their therapeutic potential in tissue engineering. [47] Confocal fluorescence imaging of MSCs incubated with 17 and irradiated at two different times, confirming the NO release occurring in the cytosol, with the fluorescence intensity correlated to the dose of NO released (Figure 9B).…”
Section: Latent Fluorescent Photocagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-molecule N-nitrosated pushpull dyes exhibit sharp onset/offset of NO release, precise dose controllable NO release, and favorable stability against biomacromolecules. [36][37][38][39][40][41][42][43][44] Yet, they still lack a high loading of NO to allow the NO release be adjusted in a large dynamic range for biomanipulation.…”
Section: Introductionmentioning
confidence: 99%